Efeitos socioculturais da transposição do rio São Francisco em comunidades rurais: a experiência de São José de Piranhas no sertão paraibano - Nascimento, Giovana Almeida (2018)
Bearing in mind the magnitude of the changes resulting from the implementation of the Transposition of the São Francisco River in the Northeast of Brazil, this thesis aims at describing and reflecting upon how these changes affect the everyday life of rural families (famílias sitiantes) displaced from the Sítio Riacho Boa Vista in the sertão of Paraíba. Thus, in order to understand these changes, we conducted a review of anthropological literature that discusses the sociocultural impacts caused by the implementation of large governmental projects. Hence, through this study, it was possible to understand that the life trajectory of these rural families was affected by several situations imposed by a compulsory displacement and that these families have been seeking resistance strategies to keep their way of life.